Transmission power consumption management for zigbee healthnets - Habaebi, Mohamed Hadi; Elashaal, Zahra A. (IIUM Press, 2011)
In clinical diagnostics and patient's treatment, many physiological parameters, referred to as emergency vital signs or EVS such as blood gas, invasive blood pressures, pulse rate, temperature, electrocardiogram (ECG), etc, have to be detected, measured and monitored. Wireless ZigBee networks utilize digital data to enable such novel clinical applications. With the use of small portable computers at other locations within the hospital or elderly nursing home, medical staff would be able to monitor a patient regardless of her position as long as she is connected to the network. Sometimes battery operated sensors are embedded into the patient's body, hence replacing the sensor's battery is done by a surgical operation. In such scenarios, it is important to prolong the battery's life as much as possible. In This paper, a simple yet effective method that can be used to reduce power consumption of wireless sensor nodes is presented. Power consumption is measured while doing data transmission, reception or in idle state. Depending on the estimated distance calculated from the averaged received signal strength Indicator (RSSI), the transmission power needed were computed and used for each packet transmission. Hence, instead of transmitting in full pmver regardless of the location of the receiving node, the transmission power is carefully controlled depending on the estimated distance.